PENGGUNAAN MEDIA PEMBELAJARAN VIDEOSCRIBE UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR SENI RUPA SISWA DI KELAS VIII2 SMP N 3 PADANG - Rio Rul Setiawan, Drs. Suib Awrus, M.Pd., Dr. Ramalis Hakim, M.Pd. (Serupa The Journal of Art Education, 2019)
The purpose of this study was to improve the interest and learning outcomes of art students in class VIII2 SMP N 3 Padang by using Videoscribe learning media. The data of this study are quantitative data. The data sources of this study are the results of teacher observation, student observation,  interest questionnaires, and learning outcomes tests. Data was collected using the method of  observation, questionnaires, and tests. The research findings, namely the use of Videoscribe  learning media, can increase the interest and learning outcomes of art students in class VIII2 of SMP N 3 Padang.Kata kunci : media, Videoscribe, minat, hasil, belajar